2008
DOI: 10.1021/jp805600k
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Laccase on the Surface of Nanoporous Gold and the Direct Electron Transfer between Them

Abstract: Nanoporous gold (NPG) with different pore sizes was obtained by simple dealloying and thermal annealing methods. The morphology of the NPG was characterized by scanning electron microscopy and nitrogen adsorption technique. Laccase was immobilized on the surface of the NPG by physical adsorption. Detailed studies were made on the effect of the pore size on laccase immobilization. NPG with pore size of 40−50 nm was demonstrated to be a suitable support for laccase immobilization. Compared with free enzyme, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(106 citation statements)
references
References 27 publications
6
93
1
6
Order By: Relevance
“…Firstly, enzymes confined within NPG display higher stability on exposure to high temperatures [49,50] and organic solvents [38] due to the nanopore providing a protective environment to the enzyme. After incubation at 50 °C for 2 h, only 6% of the initial activity of free laccase remained 35 in comparison to 60% for laccase immobilised on NPG [49].…”
Section: Properties Of Dealloyed Npg For Bioelectrochemical Applicatimentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, enzymes confined within NPG display higher stability on exposure to high temperatures [49,50] and organic solvents [38] due to the nanopore providing a protective environment to the enzyme. After incubation at 50 °C for 2 h, only 6% of the initial activity of free laccase remained 35 in comparison to 60% for laccase immobilised on NPG [49].…”
Section: Properties Of Dealloyed Npg For Bioelectrochemical Applicatimentioning
confidence: 99%
“…After incubation at 50 °C for 2 h, only 6% of the initial activity of free laccase remained 35 in comparison to 60% for laccase immobilised on NPG [49]. The activity of xylanase immobilised on NPG was assayed at 50 °C and exhibited only a 25% loss after 10 cycles [39].…”
Section: Properties Of Dealloyed Npg For Bioelectrochemical Applicatimentioning
confidence: 99%
“…Other favorable characteristics of nanoporous materials, in general, include the stabilization of the immobilized enzyme against denaturation, better thermal stability, and reduction in leaching [136,137]. Porous materials have been shown to be a good support for the immobilization of enzymes because the constrained environment can help stabilize the macromolecule under otherwise denaturing environments such as in an organic solvent or at high temperatures [138,139]. The research groups of Wang et al, for example, have recently studied the thermal and organic solvent stability of enzymes (lipase, 5 nm; catalase, 10 nm; and horseradish peroxidase, 4 nm) immobilized in nanoporous gold with an average pore size of 35 nm and concluded that they "demonstrated remarkable catalytic performance and stability" [139].…”
Section: Dna Sensorsmentioning
confidence: 99%
“…Improved attachment of the np-Au film to GC has been reported by dropping a suspension of Nafion © on a dry np-Au / GC electrode. 9,26 This, however, would preclude the ability to modify the np-Au with thiols or any other potential linker molecules.…”
Section: Voltammetric Characterization Of Cyt C Immobilized On Planarmentioning
confidence: 99%